Administrative competences in the quality of service in educational institutions of the initial level - Núñez Lira, Luis Alberto (2019)
We sought to determine the influence of the administrative competences developed by the directors on the quality of the educational service offered by the educational institutions of the initial level in the UGEL 7. This study is within the positivist model and is basic-substantive with an explanatory level and a transversal and nonexperimental design. There were 155 teachers from the initial level who made up a random, simple probabilistic sample. Two scales of opinion or perception were applied as instruments for data collection whose validity and reliability were previously established; the data were processed statistically by regression analysis. It was found that 71.3% of the initial teachers perceived that administrative competences had been developed in the directors of the district IEIs and that 85% of the initial teachers perceive that the service they provide in their school is of high quality and for 12.5% the service is of quality, concluding that the influence of the administrative abilities of the directors was 45.63% and on the perception of high quality in the service provided in the educational institutions of the initial level of the UGEL 07.